Regulatory incoherence in nutrition labelling of prepackaged food in ASEAN: What next? - Evelyn Shyamala, Paul Devadason; Chandran, V.G.R. (2018)
Regulatory heterogeneity (Pettman, 2013; USAID, 2013; Noraini, 2014) is identified as a challenge for increasing trade, harmonizing standards, and ultimately creating a single integrated Association of Southeast Asian Nations (ASEAN) market, which was a major objective in the formation of the ASEAN Economic Community (AEC) in 2015. One diverse technical regulation that governs the prepackaged food and beverage (PPF) industry is nutrition labelling. The labelling regulations across the AMS rest on the different International Guidelines followed by Member countries when preparing national regulations. Kasapila and Sharifudin (2011) point out that for nutrition labelling, Singapore, Malaysia, Brunei, Laos, Vietnam and Cambodia have followed the Codex1 guidelines in preparing their regulations. Conversely, Thailand and the Philippines, to some extent have adapted the United States (US) nutrition labelling guidelines. Even within those Member countries that adopt Codex, there are differences in the regulatory regime. Malaysia made nutrition labelling mandatory for energy, protein, carbohydrate, fat and total sugars for foods that are commonly consumed, and for various types of beverages in 2005 (AFBA, 2014; Kasapila and Sharifudin, 2011; see also Pettman, 2013). Nutrition labelling is also mandatory in the Philippines and Thailand, for certain food items. For other ASEAN countries that follow the Codex guidelines, nutrition labelling is voluntary; if nutrition and/or health claims are made on food packaging or if the food is for a special purpose (diabetic and fortified foods), nutrition labelling would then be mandatory.